Schoolcube: Gamification for Learning Management System through Microsoft SharePoint. (3rd June 2015) - Azmi, Mohd Amir; Singh, Dalbir
Abstract : A Learning Management System (LMS) is a system which acts as an integrated platform for the management of the learning process used to facilitate the process of communication between students and instructors. Although LMS is considered an important element in learning, most students do not utilise the system to its fullest extent, finding it more convenient if the activities carried out on the system are done outside the system. These factors have contributed to the issues as to why LMSs are not being used effectively and efficiently. With the accelerating pace of information technology, educational institutions should attempt to revolutionise their teaching techniques. Furthermore, combining gaming concepts can potentially increase the LMS's usability level helping to foster healthy competition among students and increase their interest in their daily learning. With regard to this objective, a prototype was developed as a proof of concept. The prototype is a web-based software and can be accessed via the Internet at all times. The teacher monitors the students' performance through the analysis of test results or tutorials conducted by the system. In conclusion, this study will present the modules that have been built into the system that could improve the overall process of education.